Socialization of the Ombudsman of the Republic of South Sumatra in the On The Spot Program - Azkiya Rifka Aulia Diva Ramadhanty; Ahmad Muhaimin; Rina Pebriana (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study uses a qualitative approach with a case study method. Data was collected through in-depth interviews with the Ombudsman of the Republic of South Sumatra, direct observation of field activities, and documentation studies. Data analysis was carried out with the stages of data reduction, data presentation, and conclusion drawing based on organizational communication theory and fusion communication theory from Lee Thayer. The results of the study show that the Ombudsman of the Republic of Indonesia Representative of South Sumatra implements a planned and integrative communication strategy. These stages include planning based on mapping the target area, the preparation of messages tailored to the characteristics of the community using communicative language and real case examples, as well as the use of various communication media (print, digital, and face-to-face). The On The Spot program has proven to be effective in bridging understanding through two-way communication that is dialogical and participatory. This direct interaction allows the Ombudsman to absorb aspirations in a *bottom-up*, straighten out the wrong public perception of the authority of the institution, and build public trust. This process reflects the concept of fusion communication, where there is an integration between the institutional goal of supervising public services and the individual interests of the community in obtaining fair and quality services.